2017
DOI: 10.1016/j.tcb.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting Motors: Kinesin, Dynein, and Cell Polarity

Abstract: In addition to their well-known role in transporting cargoes in the cytoplasm, microtubule motors organize their own tracks, microtubules. While this function is mostly studied in the context of cell division, it is essential for microtubule organization and generation of cell polarity in interphase cells. Kinesin-1, the most abundant microtubule motor, plays a role in the initial formation of neurites. This review describes the mechanism of kinesin-1-driven microtubule sliding and discusses its biological sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 68 publications
1
76
0
Order By: Relevance
“…Moreover, kinesin and dynein are the main motor proteins that traffic intracellular cargo along microtubules, including vesicles, organelles, protein complexes, and mRNA. 31 Previous studies revealed that disassembling microtubules leads to dysfunction in kinesin-and dynein-driven axonal transport with central nervous system injury or neurodegenerative diseases, and this compromised axonal transport is closely associated with early neurological dysfunction in ICH. 32 Similarly, we found that expression of kinesin and dynein was significantly decreased following disruption of microtubules in damaged dopamine neurons; this indicates that axonal transport in the nigrostriatal pathway was damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, kinesin and dynein are the main motor proteins that traffic intracellular cargo along microtubules, including vesicles, organelles, protein complexes, and mRNA. 31 Previous studies revealed that disassembling microtubules leads to dysfunction in kinesin-and dynein-driven axonal transport with central nervous system injury or neurodegenerative diseases, and this compromised axonal transport is closely associated with early neurological dysfunction in ICH. 32 Similarly, we found that expression of kinesin and dynein was significantly decreased following disruption of microtubules in damaged dopamine neurons; this indicates that axonal transport in the nigrostriatal pathway was damaged.…”
Section: Discussionmentioning
confidence: 99%
“…1b [8,9]. Parallel array of MTs, acting as reinforcing components with a main function of transporting electrochemical cargo, are the stiffest structural element within the axon [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Kinesins constitute a superfamily of microtubule-based molecular motor enzymes that couple the chemical energy from ATP turnover to force production for diverse cellular functions (reviewed in (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)). Kinesins are classified into 15 different subfamilies, yet they share a structurally conserved kinesin motor domain (1,3,(13)(14)(15)(16).…”
mentioning
confidence: 99%